Protecting Consumer Medicine In Indonesia: Examining The Role of Pharmacist - Norma Sari (Fakultas Hukum Universitas Islam Indonesia, 2015)
Pharmacy as a profession has been undergoing many relevant changes in facing many challenges and social demands. The consumers generally are not well-acknowledged of many drugs to consume, to increase, or to maintain their health level. This research aims at understanding the role of a pharmacist in protecting the drug consumers in Indonesia. The reserach is a normative one relying on secondary data source. The data is collected by document study through reading, studying, and identifying the data to be analyzed qualitatively. The research result concludes that the pharmacists play an important role in protecting drug consumers in Indonesia by (1) being responsible in providing (a) quality assurance, production, quality control of pharmacy industry (b) pharmaceutical services in the public pharmacy. (2) Cutting off the edge business directly facing the drug/consumers in the long chain mechanism of drug consumption.